Household affiliation of young adults in Italy and Norway. The significance of gender, sociocultural background, work and money - Tindara Addabbo; Randi Kjeldstad (Statistics Norway, Research Department, 2013)
Italy and Norway are characterized by different household patterns of young adults, with young Italians being more likely to live in their parents' house and young Norwegians more likely to live independently, alone or in multi-occupant households. This paper asks why, and how these differences can be understood. We focus on three types of household affiliation in young adulthood: Living with parents, living alone (including in multi-occupant households) and living in a couple, and conduct multivariate analyses on the interaction of gender, sociocultural background, and economic activity indicators at the individual level. We use EU SILC micro data on 2007, a time when the economic prospects and the labour market situation were relatively stable in both countries. The results show that young adults' living arrangements are differently affected by the included subset of factors in the two countries. Generally, the propensity of young adults to live with parents and not in a couple appears more sensitive to individual characteristics in Italy than in Norway. This applies both to sociocultural and economic characteristics. Whereas an important prerequisite of leaving the parental home among young (native born) Italians, and particularly among Italian men, is to have finished education and attained a permanent job, young Norwegians establish households on their own more or less in any case.
Keywords: D1; J12; J13; J16; Z13; 330; Young adults; Gender; Household affiliation; Italy; Norway